Channel Formation in Rivers Downstream of Water Reservoirs - Kirvel Ivan; Kukshinov Mikhail; Volchek Alexander; Kirvel Pavel (Limnological Review, 2018)
The article concerns the study of the influence of river reservoirs of Belarus on the evolution of river channels in their downstream pools. On the basis of observational data from the Republican Hydrometeorological Center of the Republic of Belarus (RHMC), as well as own field observations a quantitative evaluation of the change of the main channel formation factors, the direction, horizontal and vertical parameters of deformation of the riverbeds below dams has been performed. Changes in the type of channel processes for the regulated parts of rivers have also been assessed. It has been found that the investigated reservoirs accumulate up to 65% of the sediment transported by the river in a suspended state. Restoration of the water turbidity to values close to the natural regime occurs at a distance of 20 km downstream from a dam of small reservoirs, and up to 50 km downstream from a dam in the case of medium-sized reservoirs. The degree of the riverbed deformations downstream from a reservoir is defined by the geological and lithologic structure of the channel bottom deposits. If there are easily washed sand deposits at the bottom, then the dominant process is deep erosion. If sediments are more heterogenic with increased admixture of gravel-pebble material the development of directed deep erosion is reduced. The change of the existing type of channel processes of regulated rivers is due to the imbalance between the main factors of channel formation in the initial period of the operation of new water-engineering systems (5-7 years). The observed changes are typical of rivers with sandy riverbed.